Taking sides : (McGraw-Hill, 2006)
This book presents current controversial issues in a debate-style format designed to stimulate student interest and develop critical thinking skills. Each issue is thoughtfully framed with an issue summary, an issue introduction, and a postscript. An instructor’s manual with testing material is available for each volume. USING TAKING SIDES IN THE CLASSROOM is also an excellent instructor resource with practical suggestions on incorporating this effective approach in the classroom. Each TAKING SIDES reader features an annotated listing of selected World Wide Web sites and is supported by a book website. Visit www.mhcls.com.